2022
DOI: 10.3390/pathogens11010092
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles of Leishmania major Derived from Human and Rodent Hosts in Endemic Cutaneous Leishmaniasis Areas of Tunisia and Algeria

Abstract: Leishmaniasis is a protozoal vector-borne disease that affects both humans and animals. In the Mediterranean Basin, the primary reservoir hosts of Leishmania spp. are mainly rodents and canids. Lipidomic approaches have allowed scientists to establish Leishmania spp. lipid profiles for the identification of cell stage specific biomarkers, drug mechanisms of action, and host immune response. Using an in silico approach of global network interaction between genes involved in fatty acid (FA) synthesis followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In addition, Bouabid et al demonstrated the predominance of polyunsaturated fatty acids in L. major promastigote by mass spectrometry . The current study shows that the infrared spectroscopic approach corroborates the findings of the gold standard lipidomic approaches.…”
Section: Resultssupporting
confidence: 86%
“…In addition, Bouabid et al demonstrated the predominance of polyunsaturated fatty acids in L. major promastigote by mass spectrometry . The current study shows that the infrared spectroscopic approach corroborates the findings of the gold standard lipidomic approaches.…”
Section: Resultssupporting
confidence: 86%
“…In addition to the two overlapping proteins/transcripts, TFRC and NDK3, some proteins from the two different datasets appear to belong to mutual pathways and interact with each other. Remarkable examples are the subnetworks consisting of PDHX, PDK4, CYC1, BHD1, ACSL1, and ACSL3, involved in biosynthetic processes of fatty acid derivatives, purine ribonucleotides, and the tricarboxylic acid cycle, , that are shared among the DEP and DET datasets. Subsequently, ABCG2 and HMOX, networking with TFRC, ALCAM and PECAM, and AQP9 and PLEK, participate in immune response and the immune system and in vesicle-mediated trafficking .…”
Section: Resultsmentioning
confidence: 99%
“…Phospholipids (PL) have been reported as the predominant class of lipid in Leishmania sp. The fatty acid (FA) composition was characterized by a lower abundance of the precursor C18:2(n-6) [ 36 , 120 ]. Leishmania sp.…”
Section: Ltps and Their Biological Implicationsmentioning
confidence: 99%
“…Promastigote, the extracellular form of the parasite relies on de-novo synthesis of lipids (specifically, glycerophospholipid, sterols and sphingolipids), while intracellular amastigotes form largely depends on host-derived lipids for intracellular growth and survival [ 35 ]. Lipid droplets (LDs), which are observed both inside the parasitophorous vacuole and within parasite cytoplasm may indicates that L. donovani could use LDs as high energy sources for their growth [ 36 ]. The functional implications of exosomes from L. donovani during host-parasite interaction was also reported [ 123 , 124 , 125 , 126 , 127 ].…”
Section: Ltps and Their Biological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation